A dictionary of the crisis in the Philippine ecosystems - Segovia, Raul E. (Quezon City Co-Publishers: Philippine Environmental Action Network [and] Citizens' Alliance for Consumer Protection, 1995)
"The focus of the book is focused on the crisis of the ecosystems for which it is usually linked to the same conditions that have caused other forms of crisis- political,social and economic. The choice of the environment as a new terrain in the struggle for justice is only one among others. The aim of this book is to improve the reader's literacy on the environmental crisis such as floods and earthquakes, the uncollected garbage of the cities, the soil erosion of the mountains and the sedimentation of dams, the destruction of the forests, coastal zones, coral reefs, and river systems were given emphasis in order in this book." Arranged in alphabetical order.
Keywords: Environmental degradation -- Philippines; Man -- Influence of environment; Philippines -- Environmental conditions